Coordination arrival control for multi-agent systems - Li, R.; Shi, Y.; Teo, Kok Lay (John Wiley and Sons Ltd, 2015)
The coordination arrival problems of first-order multi-agent systems with the arriving structure and the time structure requirements are considered for the cases with no obstacle and obstacle. To describe the distributed coordination arrival problems, we first introduce needed definitions, such as coordination arrival, threat point, and arrival structure. By selecting the estimated value of the arriving time of the agent as variable, we then develop a central estimating algorithm, which is used to construct the arriving protocols. Based on the estimating algorithm, we build and analyze coordination arriving protocols for the proposed coordination arrival problems. Several simulation examples are presented to validate the proposed algorithms.